Immunological relationship between delta-hemolysins of Staphylococcus aureus and coagulase-negative strains of staphylococci. - Turner, W H (1979)
Delta-hemolysin of coagulase-negative staphylococcal strains was immunologically identical to delta-hemolysin of Staphylococcus aureus (Newman) but distinct from delta-hemolysin from a canine strain of S. aureus.